On properties of the second order generalized autoregressive GAR(2) model with index. - Shitan, Mahendran; Peiris, Shelton (Elsevier, 2009)
In this paper we consider a new class of time series models generated by a second order autoregressive type operator with an index. Autocorrelation and spectral properties are discussed and some explicit results are derived for a restricted class in the family. The parameter estimation is discussed using the Whittle procedure. Some numerical results are presented to support the theoretical results.